Karya Digital dan Perlindungan Hak Kekayaan Intelektual Di Era Digital - Evelyn Angelita Pinondang Manurung (Verdict: Journal of Law Science, 2022)
Digital Works and Protection of Intellectual Property Rights in the Digital Age Advances in technology and information today have a significant impact on changes in human life. The digital era today is very dependent on internet-based technology media. The existence of internet-based platforms has brought people closer to the digital world. Changes in the dynamics of the society in a digital society, of course, have an impact on the knowledge or understanding of the community on the legal impact of the use of digital platforms, such as knowledge of one's intellectual property rights on digital media. Work that was still physically in the form of now turned into digital media or digital copyright works. In this case, the regulations governing the intellectual property rights of a person/organization should accommodate and protect the digital intellectual creation of the Indonesian people as a form of legal protection for the rights possessed by the owner of the Cipta work. This study aims to protect intellectual property rights in digital-based products/works. This study uses a normative juridical research method using the source of literature, including applicable laws, legal literacy, and other legal materials. Technological advances have made it easier for everyone to steal and duplicate the digital work of others to make a profit. Therefore, the existence of an existing legal umbrella and policy, namely Law Number 11 of 2008 concerning Information on Electronic Transactions and Law Number 28 of 2014 concerning Copyright, is expected to increase innovation increase competitiveness in the digital era and support the protection of rights of Intellectual Property for Digital Work for all parties who are entitled.